Understanding agoraphobic avoidance: the development of the Oxford Cognitions and Defences Questionnaire (O-CDQ). Issue 3 (15th May 2022) - Rosebrock, Laina; Lambe, Sinéad; Mulhall, Sophie; Petit, Ariane; Loe, Bao S; Saidel, Simone; Pervez, Maryam; Mitchell, Joanna; Chauhan, Nisha; Prouten, Eloise; Chan, Cindy; Aynsworth, Charlotte; et al.
Abstract: Background: Many patients with mental health disorders become increasingly isolated at home due to anxiety about going outside. A cognitive perspective on this difficulty is that threat cognitions lead to the safety-seeking behavioural response of agoraphobic avoidance. Aims: We sought to develop a brief questionnaire, suitable for research and clinical practice, to assess a wide range of cognitions likely to lead to agoraphobic avoidance. We also included two additional subscales assessing two types of safety-seeking defensive responses: anxious avoidance and within-situation safety behaviours. Method: 198 patients with psychosis and agoraphobic avoidance and 1947 non-clinical individuals completed the item pool and measures of agoraphobic avoidance, generalised anxiety, social anxiety, depression and paranoia. Factor analyses were used to derive the Oxford Cognitions and Defences Questionnaire (O-CDQ). Results: The O-CDQ consists of three subscales: threat cognitions (14 items), anxious avoidance (11 items), and within-situation safety behaviours (8 items). Separate confirmatory factor analyses demonstrated a good model fit for all subscales. The cognitions subscale was significantly associated with agoraphobic avoidance ( r = .672, p < .001), social anxiety ( r = .617, p < .001), generalized anxiety ( r = .746, p < .001), depression ( r = .619, p < .001) and paranoia ( r = .655, p < .001). Additionally, both the O-CDQ avoidance ( r = .867, p < .001) and within-situation safety behaviours ( r = .757, p < .001) subscales were highly correlated with agoraphobic avoidance. The O-CDQ demonstrated excellent internal consistency (cognitions Cronbach's alpha = .93, avoidance Cronbach's alpha = .94, within-situation Cronbach's alpha = .93) and test–re-test reliability (cognitions ICC = 0.88, avoidance ICC = 0.92, within-situation ICC = 0.89). Conclusions: The O-CDQ, consisting of three separate scales, has excellent psychometric properties and may prove a helpful tool for understanding agoraphobic avoidance across mental health disorders.